Analisis Manajemen Risiko Terhadap Keberlangsungan Usaha UMKM Kos-kosan di Kota Bandung (Kosan OYE) - Marlina, Auriel Putri; Murdani, Yusuf; Ibrahim, Hammam Rizky (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Every business that is undertaken will irnevitably face competition in order to grow. Small and medium enterprises, commonly referred to as SMEs, are businesses that are relatively easy for anyone with the desire to start a business to run. Competition will always exist in every aspect of life, including SMEs. Every business faces competition and challenges that must be addressed. To deal with competition and challenges in the business world, every SME must conduct market research and develop human resources and technology. Every business also involves risk. Therefore, SMEs need to understand what risk management is. Risk management is necessary to anticipate or reduce the likelihood of risks occurring in a business. This paper aims to describe the risks faced by the SME boarding house "OYE" in Bandung. The analysis method uses descriptive analysis obtained from interviews with the owner of the SME boarding house "OYE" in Bandung. The analysis results show that the owner of the SME boarding house "OYE" in Bandung faces several risks: compliance and legal risk, financial risk, marketing risk, security risk, and operational risk. Based on the SWOT analysis of the SME boarding house "OYE" in Bandung, its strengths include having facilities that are above the average of boarding houses in the surrounding area. Its weaknesses include the lack of an effective marketing strategy. An innovation is seen in its design, which adopts a modern and comfortable style to attract millennial and Gen Z tenants. The threats faced by the "OYE" boarding house business include problematic tenants or those who damage property, which can disrupt operations.